From Periphery to Nexus: Decoding Borderland Agency in Reshaping Transnational Fragrance Value Chains - Empirical Evidence from Yunnan’s Plant-Based Aroma Industry - ZHOU, Xinmei; FENG, Renjie; TU, Huazhong (Pacific International Journal, 2025)
This article explores the fragrance and flavour industry from a global perspective, particularly focusing on the cooperation and development in Yunnan and the Lancang-Mekong region (Myanmar, Laos, Thailand, Cambodia, Vietnam). Yunnan, as the main production area for natural spices in China, boasts rich spice resources and policy advantages, yet it remains at the lower end of the global industry chain. The countries in the Lancang-Mekong region occupy a significant position in the global spice supply chain due to their unique geographical and climatic conditions. Through comparative analysis methods, combined with theories of regionalism, competitive advantage, and international competitiveness, this article examines the competitiveness of the fragrance and flavour industry in the Lancang-Mekong region, and proposes development suggestions such as strengthening regional cooperation, enhancing technological innovation capabilities, and building brands. The research indicates that through the Lancang-Mekong cooperation mechanism, resource sharing, technological exchange, and brand internationalisation can be promoted, thereby driving the green and sustainable development of the regional spice industry.